2014
DOI: 10.1002/2013wr014905
|View full text |Cite
|
Sign up to set email alerts
|

Revealed and stated preference valuation and transfer: A within‐sample comparison of water quality improvement values

Abstract: Benefit transfer (BT) methods are becoming increasingly important for environmental policy, but the empirical findings regarding transfer validity are mixed. A novel valuation survey was designed to obtain both stated preference (SP) and revealed preference (RP) data concerning river water quality values from a large sample of households. Both dichotomous choice and payment card contingent valuation (CV) and travel cost (TC) data were collected. Resulting valuations were directly compared and used for BT analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…For the realized preference sample, mean WTP was estimated at 39 cents (lower CI = −14; upper CI = 193), truncated mean was 149 cents (lower CI = 25; upper CI = 4821), and median was 39 cents (lower CI = −103; upper CI = 192). While WTP estimates from the realized preference sample were lower, overlapping confidence intervals indicated that these results were not significantly different (Ferrini et al, ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For the realized preference sample, mean WTP was estimated at 39 cents (lower CI = −14; upper CI = 193), truncated mean was 149 cents (lower CI = 25; upper CI = 4821), and median was 39 cents (lower CI = −103; upper CI = 192). While WTP estimates from the realized preference sample were lower, overlapping confidence intervals indicated that these results were not significantly different (Ferrini et al, ).…”
Section: Resultsmentioning
confidence: 98%
“…We compared mean and median WTP and associated CIs estimated from stated and realized preference methods (Ferrini, Schaafsma, & Bateman, ). We used a chi‐square statistical test to determine whether the deviations between the expected numbers of individuals who indicated their willingness to pay a price premium on the CV survey were different from the number who actually paid a price premium (Carlsson, Garcia, & Lofgren, ).…”
Section: Discussionmentioning
confidence: 99%
“…The payment vehicle was presented as a hypothetical increase to the respondents' annual domestic water bill. The payment vehicle corresponded with those used in previous studies on water quality improvements in public areas [11,24]. We believed that this approach would be most appropriate as, in the UK, domestic water bills also include a sum towards improving wastewater services that, in turn, leads to improved river water quality.…”
Section: Survey Instruments and Choice Experiments Designmentioning
confidence: 99%
“…However, the model function contains distance, a key element for transferability, and the dataset includes other useful variables, such as income. Previous research [24] has suggested that in most cases, differences between WTP estimates obtained by different methods (e.g., travel cost or contingent valuation) are larger than differences due to dissimilar river characteristics: when multiple studies are available, welfare estimates for rivers that have similar characteristics, but are based on different methods, consistently result in larger errors than transfers across space, keeping the method constant. With this in mind, it may be beneficial in the future to assess our results against those obtained by studies that use similar methods and were undertaken at rivers with similar characteristics.…”
Section: Research Limitationsmentioning
confidence: 99%
“…Among these tools, revealed preference and stated preference techniques are usually applied to estimate ecosystem services that lack a market value, such as recreation. Revealed preference methods infer values from observed behavior, and thus, from actual choices people make within markets (Boyle, 2003;Ferrini et al, 2014). Stated preference methods attempt to establish non-market values using survey questions, usually by asking respondents to choose between different scenarios (Brown, 2003;Metcalfe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%